Trombe Wall Application with Heat Storage Tank - Topçuo?lu, K?vanç (Salehan Institute of Higher Education, 2019)
In this study, an investigation was made of the performance of a Trombe wall of classical structure used together with a heat store. Most Trombe walls are able to supply the heating needs of a space to which they are connected without the need for extra heating at times when the sun is shining. However, the heat obtained from the Trombe wall can be in excess of needs at such times, and measures must be taken to provide ventilation to the heated space. It is thought that the heat energy can be used more efficiently and productively by storing the excess heat outside the building and using it inside the building when there is no sunlight. To this purpose, a tank full of water and marble was built as a heat store as an alternative to the general Trombe wall design, and an attempt was made to minimise heat losses by burying it in the ground. It was concluded that in place of a traditional Trombe wall system using a massive wall heat store, a heat store could be constructed in a different position and with different materials. The Trombe wall system which was developed and tested met up to 30% of the energy needed for heating and cooling the building, and reduced the architectural and static disadvantages of Trombe wall systems. As a result of the study, it was seen that where a standard reinforced concrete wall could supply heat to the inside for 7 hours and 12 minutes, the figure for a wall made of paraffin wax was 8 hours and 55 minutes. In the same study, the heat storage thickness of a reinforced concrete wall was calculated as 20 cm, while that of a paraffin wax wall was calculated as 5 cm.